Food security's broken link: The misalignment of stakeholder priorities in agriculture and nutrition in Vihiga County, Kenya - Kilelo, E.S.; Nowicki, Marcin; Nguka, G.; Olimba, Lilian Aluso; Konyole, S.O.; Termote, Céline (African Scholarly Science Communications Trust, 2023)
Global food security will exist when all people, at all times, have physical and economic access to sufficient, safe and nutritious food to meet their dietary needs and food preferences for an active and healthy life. Today, about 2 billion of the 7.96 billion people on Earth are food insecure. Food insecurity is still a challenge in Kenya despite different sectors' interventions in nutrition and agriculture. This study sought to identify programs and stakeholders who are influential on food security by analyzing farmers' participation in programs, the link between agriculture and nutrition goals, factors that influence the success of programs, and the impact of policy on food security. The study adopted a descriptive cross-sectional design using mixed methods of data collection. Qualitative data were obtained from thirty purposively selected stakeholders through focus group discussions and key informant interviews. The themes formed from the qualitative data were analyzed manually, and verbatim quotes were used to explain the findings. Additionally, two hundred and seventy-three structured questionnaires were administered to farmers to collect quantitative data. The data revealed that (75%) of farmers were beneficiaries of key programs. Pearson's chi-square test gave x^2(4, n=273)>=91.045, with a p-value of 0.000 which is less than 0.05, indicates a strong relationship between education level and farmers' awareness of key agricultural programs. The primary motivation in agriculture production was income generation, but the nutritional value of the food was overlooked. Poor collaboration among stakeholders was shown to not only result in unequal program coverage but also pose an obstacle in aligning agricultural programs with local nutrition demands. Moreover, although food and agriculture policies are in place, gaps exist in implementing and adhering to these policies. It was revealed that budget allocation to the agriculture sector is at (2.4 %) which is still a quarter way to the international commitment of (10%). Lastly, land ownership limitations hinder smallholder farmers' ability to meet income and nutrition needs, as approximately a third of those surveyed (n=136, 35.5%) reported owning less than 0.5 acres of land. It is, therefore, necessary to build the capacity to support smart agriculture, using technological methods to increase productivity on small land. Additionally, stakeholders must create policy strategies, collaboration and program distribution mechanisms to promote nutrition and agriculture to improve food security. Key words: Agriculture, Food Security, Influence, Linkage, Nutrition, Program, Policy, Stakeholders